Desenvolvimento de um modelo estacionário para o escoamento bifásico líquido-gás em golfadas com transferência de calor em tubulações horizontais - Bassani, Carlos Lange (2014)
Multiphase flows occur in many industrial applications such as vapor heaters, condensers and in gas and oil production. A common liquid-gas multiphase flow is the intermittent or slug flow, characterized by the succession of liquid slug and elongated bubbles along the pipe. Due to the high complexity of the phenomena, the literature presents only a few mathematical models for simulation of the temperature distribution along the pipe and for the two-phase flow heat transfer coefficient prediction. In this context, the present work develops a stationary mathematical model for gas-liquid two-phase slug flow with heat transfer in horizontal pipes. The mass, momentum and energy conservation equations are applied to control volumes located at the different regions of the slug flow unit cell. The mathematical model uses the mixture temperature as the main variable and also takes into account the heat transfer between two consecutive unit cells, known as thermal scooping. Two different thermal boundary conditions were used in the model, constant external temperature and constant heat flux. The model was implemented in Fortran language and validated with experimental data from the literature. The temperature drop along the pipeline shows good agreement with experimental data, with a precision of 15 %. Furthermore, an expression for the two-phase heat transfer coefficient was developed and showed an accuracy of 30 % with experimental data and good agreement with some literature correlations, within 10 to 20 % of concordance.